Rancang Bangun Sistem Informasi Customer Loyalty untuk Keunggulan Kompetitif Organisasi - Mulyani, Sri; Mustafid, Mustafid; Widodo, Catur Edi (JSINBIS (Jurnal Sistem Informasi Bisnis), 2012)
Utilization of information technology to achieve competitive advantage has become a necessity  for business people and managers of organizations  in the information age now. This research aim to create a customer loyalty that the information system is one part of theCustomer  Relationship  Management  to  collect  data  on  indicators  of  customer  loyalty.  Indicator  of  customer  loyalty  is  determined according  empirical  model  customer  loyalty  and  create  customer  loyalty  information  system  that  can  be  used  to  gain  competitive advantage organizations. Structural Equation Modeling is used to obtain indicators of customer loyalty. Customer loyalty info rmation system designed using prototype system development and modeling analysis using Data Flow Diagram, database design using  Entity Relationship  Diagram,  and  a  web-based  interface.  Web-based  information  systems  that  provide online  customer  survey  facilities  and analysis  results  in  the  form  of  customer  loyalty  index  values  shaped  by  the  dynamic  graphic  indicator  of  loyalty  according  to  the empirical study of customer loyalty that can be used to gain competitive advantage. The value of customer loyalty index cons ists of four main variables, namely: the ability to anticipate customer value, customer value anticipation peace, customer satisfaction, and loyalty.Keywords: Customer loyalty, Structural Equation Modeling, Index loyalty, Competitive advantage